2017
DOI: 10.1101/226175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host shifts result in parallel genetic changes when viruses evolve in closely related species

Abstract: 16Host shifts, where a pathogen invades and establishes in a new host species, are a major source of 17 emerging infectious diseases. They frequently occur between related host species and often rely on were genetically more similar to each other than to lineages from other host species. When we 23 compared viruses that had evolved in different host species, we found that parallel genetic changes 24 were more likely to occur if the two host species were closely related. This suggests that when a 25 virus adap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Most mutations were deleterious in the original and taxonomically related hosts, and a larger fraction of mutations were beneficial in hosts from unrelated families, in which the fitness of the wild type TEV genotype was low. In agreement with these results, it has been shown that adaptation to a new host may result in adaptation to closely related hosts, which will favour virus jumps to related species [15]. In another study, seven genotypes of pepper mild mottle virus (PMMoV) with coat protein mutations determining the overcoming of different resistance alleles in pepper, were assayed in five susceptible pepper genotypes [16 ].…”
Section: Virus-intrinsic Factors In Host Range Evolutionmentioning
confidence: 67%
“…Most mutations were deleterious in the original and taxonomically related hosts, and a larger fraction of mutations were beneficial in hosts from unrelated families, in which the fitness of the wild type TEV genotype was low. In agreement with these results, it has been shown that adaptation to a new host may result in adaptation to closely related hosts, which will favour virus jumps to related species [15]. In another study, seven genotypes of pepper mild mottle virus (PMMoV) with coat protein mutations determining the overcoming of different resistance alleles in pepper, were assayed in five susceptible pepper genotypes [16 ].…”
Section: Virus-intrinsic Factors In Host Range Evolutionmentioning
confidence: 67%
“…The influence of these factors depends on the viral population’s life history and, therefore, careful consideration is needed to design and interpret evolutionary experiments to study the evolutionary potential of viruses and inform prediction. In the context of strong selection on specific phenotypes, the evolutionary response to selection is often repeatable and involves only a few mutations (Longdon et al, 2017; Morley and Turner, 2017; Stern et al, 2017; Weinreich et al, 2006; Xiao et al, 2017; Xue et al, 2017). However, when considering more complex outcomes, such as spillover events, environmental and epidemiological factors add layers of additional complexity that must be considered (Campbell et al, 2018; Geoghegan and Holmes, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We used Drosophila C virus (DCV) strain B6A (Longdon et al., 2018), which is derived from an isolate collected from D. melanogaster in Charolles, France (Jousset et al., 1972). The virus was prepared as described previously (Longdon et al., 2013).…”
Section: Methodsmentioning
confidence: 99%